Antioxidant activities, total phenolic and flavonoid contents of ethyl acetate extract of Mengkudu (Morinda citrifolia, L) fruit and its fractions - Rohman, Abdul; Riyanto, Sugeng; Utari, Diah (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2006)
This present study was carried out to evaluate antioxidant activities, total phenolic and total flavonoid contents of ethyl acetate extract of Mengkudu fruit and its fractions. Ethyl acetate extract was fractionated by column chromatography and yielded 15 fractions based on the identical TLC (thin layer chromatography) profile.Antioxidant activities in ethyl acetate extract and its fractions were determined by radical scavenging assay using DPPH (2,2-diphenyl-1- picrylhydrazyl) radical. The total phenolic and total flavonoid contents were determined spectrophotometrically.Among 15 fractions of ethyl acetate extract evaluated, fraction 8 (IC50 5,49 μg/mL) and fraction 7 (IC50 7,90 μg/mL) revealed antioxidant activities that higher than that of vitamin E (IC50 8,27 μg/mL). The total phenolic contents ranged from 5.94 ± 0.08 to 36.52 ± 0.35 g of gallic acid equivalent/100 gram dry material whereas the total flavonoid contents ranged from 1.19 ± 0.02 to 17.65 ± 0.17 g of quercetin equivalent/100 gram dry material.A linier positive relationship existed between the antioxidant activities and total phenolic contents of the tested ethyl acetate extract and its fractions y = -1.220x + 44.022; r2 = 0.67, while the correlation between antioxidant activities and total flavonoid contents revealed a linier regression y = -2.202 x + 35.82; r2 = 0.4278.Key words: antioxidant activity, Morinda citrifolia, L, Fraction